Steel fiber reinforced self-compacting concrete thin slabs – Experimental study and verification against Model Code 2010 provisions. (1st September 2016) - Facconi, Luca; Minelli, Fausto; Plizzari, Giovanni
Highlights: Tests on 8 very thin simply supported slabs reinforced with high strength steel fibers only. High capacity of energy absorption by FRC slabs. Demonstration of the ability of FRC in providing a ductile response in slender plates. Benefits of hybrid reinforced concrete structures containing high strength steel fibers. Verification of experimental results against Model Code 2010. Abstract: This paper reports the experimental results of 11 full scale thin plates (dim. 4200 × 2500 × 80 mm 3 ): 8 slabs containing three types of fiber reinforcement (2 types of high strength fibers, one added in two different contents) were tested first. Then, one slab cast with traditional reinforced concrete was tested and used as a reference slab. Finally, two slabs were produced with a typical rectangular opening, which determines a disturbed stress region: the first one was cast in classical reinforced concrete (RC) whereas the second by suitably combining fibers and rebars under a hybrid reinforced concrete (HRC) perspective. Results show that these slender plates, undergoing light loads, might be an effective structural application in which fibers could represent the unique flexural reinforcement. In presence of disturbed regions due to openings, frequent in practice, a suitably combination of rebars and fibers is proposed and discussed. Emphasis on cracking phenomena and energy absorption capacity is provided. A comparison with the requirements of the fib Model Code 2010 for members containing only fibers is subsequently discussed.